2018
DOI: 10.1039/c8py00715b
|View full text |Cite
|
Sign up to set email alerts
|

Fully alternating and regioselective ring-opening copolymerization of phthalic anhydride with epoxides using highly active metal-free Lewis pairs as a catalyst

Abstract: Cooperative metal-free Lewis pairs effectively catalysed controlled ring-opening copolymerization of phthalic anhydride (PA) with epoxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 77 publications
5
57
0
Order By: Relevance
“…In the previous reports, at least 1 equiv of TEB relative to base was generally required for efficient catalytic ROAC reactions . It was surprising that for the current catalytic system even a little amount of TEB can efficiently accelerate the copolymerization (Table , Run 5 vs. Run 1).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In the previous reports, at least 1 equiv of TEB relative to base was generally required for efficient catalytic ROAC reactions . It was surprising that for the current catalytic system even a little amount of TEB can efficiently accelerate the copolymerization (Table , Run 5 vs. Run 1).…”
Section: Resultsmentioning
confidence: 89%
“…Recently, Zhao and coworkers reported the one‐step synthesis of polyester–polyether block copolymers by ROAC of PA and PO/EO using a mild phosphazene base with TEB . Chakraborty and coworkers systematically tested various Lewis acids, such as TEB, Al(CH 3 ) 3 , Et 2 Zn, and n ‐Bu 2 Mg, in combination with various Lewis bases, such as PPNCl, 4‐( N,N ‐dimethylamino)pyridine, 1,8‐diazabicyclo[5.4.0]undec‐7‐ene, and TBD, as Lewis pair catalysts for ROAC of anhydrides and epoxides . It was found that the TEB/PPNCl pair stood out as the most active and effective one for the perfectly alternating and regionselective controlled ROAC of various epoxides with anhydrides.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, PPF has been synthesized by step‐growth polymerization, which requires both elevated temperature and reduced pressure, and typically results in modest yields, broad molecular mass distribution ( Ð M ), and byproducts that must be removed prior to use . Various copolymerization strategies of epoxides, anhydrides, and lactones have been investigated previously to produce a wide range of polyesters . Recently, PPF was synthesized using an alternating ring‐opening copolymerization (ROCOP) of maleic anhydride (MA) and propylene oxide (PO) to produce poly(propylene maleate) (PPM), which was subsequently isomerized to produce PPF .…”
Section: Methodsmentioning
confidence: 99%
“…[24,25] Tr aditionally,P PF has been synthesized by step-growth polymerization, which requires both elevated temperature and reduced pressure,a nd typically results in modest yields, broad molecular mass distribution ( M ), and byproducts that must be removed prior to use. [27][28][29][30] Recently,P PF was synthesized using an alternating ring-opening copolymerization (ROCOP) of maleic anhydride (MA) and propylene oxide (PO) to produce poly(propylene maleate) (PPM), which was subsequently isomerized to produce PPF. [27][28][29][30] Recently,P PF was synthesized using an alternating ring-opening copolymerization (ROCOP) of maleic anhydride (MA) and propylene oxide (PO) to produce poly(propylene maleate) (PPM), which was subsequently isomerized to produce PPF.…”
mentioning
confidence: 99%
“…[26] Va rious copolymerization strategies of epoxides,a nhydrides,a nd lactones have been investigated previously to produce aw ide range of polyesters. [27][28][29][30] Recently,P PF was synthesized using an alternating ring-opening copolymerization (ROCOP) of maleic anhydride (MA) and propylene oxide (PO) to produce poly(propylene maleate) (PPM), which was subsequently isomerized to produce PPF. [31][32][33][34] This approach results in am uch higher degree of control of the material properties and the use of two monomer species offers multiple sites for post-polymerization chain functionalization.…”
mentioning
confidence: 99%